PENERAPAN MODEL PEMBELAJARAN COOPERATIVE SCRIPT UNTUK MENINGKATKAN KETERAMPILAN MEMBACA TEKS PUISI PADA PESERTA DIDIK KELAS II SDN SEGOROMADU - Agustin Nur Khafidah; Afakhrul Masub Bakhtiar (JUSEDA, 2020)
This study aims to determine the process of applying cooperative script learning models to improve the skill of reading poetry texts to second grade students of SDN Segoromadu. The results of the study obtained in the action of the first cycle showed that the results of the students' poetry reading skills were still under the KKM with a percentage value of 60%. Whereas in the second cycle of action in the application of cooperative script learning models can improve students' poetry reading skills with a percentage value of 75%.